In Vivo Insulin Sensitivity and Secretion in Obese Youth: What are the differences between normal glucose tolerance, impaired glucose tolerance, and type 2 diabetes? - Bacha, Fida (American Diabetes Association, 2009)

(untitled)
OBJECTIVE—Impaired glucose tolerance (IGT) represents a pre-diabetic state. Controversy continues in regards to its pathophysiology. The aim of this study was to investigate the differences in insulin sensitivity (IS) and secretion in obese adolescents with IGT compared with those with normal glucose tolerance (NGT) and type 2 diabetes. RESEARCH DESIGN AND METHODS—A total of 12 obese adolescents with NGT, 19 with IGT, and 17 with type 2 diabetes underwent evaluation of insulin sensitivity (3-h hyperinsulinemic [80mu/m(2)/min]–euglycemic clamp), first-phase insulin and second-phase insulin secretion (2-h hyperglycemic clamp), body composition, and abdominal adiposity. Glucose disposition index (GDI) was calculated as the product of first-phase insulin × insulin sensitivity. RESULTS—Insulin-stimulated glucose disposal was significantly lower in subjects with type 2 diabetes compared with subjects with NGT and IGT, with no difference between the latter two. However, compared with youth with NGT, youth with IGT have significantly lower first-phase insulin and C-peptide levels and GDI (P = 0.012), whereas youth with type 2 diabetes have an additional defect in second-phase insulin. Fasting and 2-h glucose correlated with GDI (r = −0.68, P < 0.001 and r = −0.73, P < 0.001, respectively) and first-phase insulin but not with insulin sensitivity. CONCLUSIONS—Compared with youth with NGT, obese adolescents with IGT have evidence of a β-cell defect manifested in impaired first-phase insulin secretion, with a more profound defect in type 2 diabetes involving both first- and second-phase insulin. GDI shows a significantly declining pattern: it is highest in NGT, intermediate in IGT, and lowest in type 2 diabetes. Such data suggest that measures to prevent progression or conversion from pre-diabetes to type 2 diabetes should target improvement in β-cell function.